Disseminated Streptococcus anginosus invasive infection with intracranial subdural abscess formation. Issue 5 (May 2022) - Suzuki, Tetsuya; Morioka, Shinichiro; Nomoto, Hidetoshi; Takaya, Saho; Ishikane, Masahiro; Yanagisawa, Shunsuke; Hayakawa, Kayoko; Ohmagari, Norio
Abstract: We report the case of a 67-year-old woman with disseminated Streptococcus anginosus invasive infection. Even under a maximal dose of susceptible antibiotics, her condition was complicated by pulmonary septic emboli and intracranial subdural abscess. Effective antibiotics and emergent surgical drainage were performed, but the sequelae of aphasia and hemiplegia remained. Underlying immunocompromised conditions of diabetes mellitus and monoclonal gammopathy of unknown significance might partially affect the clinical course of invasive S. anginosus infection. Once the infection becomes invasive, it can be refractory and difficult to treat. Clinicians should acknowledge the characteristics of invasive S. anginosus infection.